2019
DOI: 10.3802/jgo.2019.30.e61
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of gonadotropin-releasing hormone agonist combined with aromatase inhibitor as fertility-sparing treatment in obese patients with endometrial cancer

Abstract: Objective This study aims to evaluate the effects and pregnancy outcomes of gonadotropin-releasing hormone agonist (GnRH agonist) combined with aromatase inhibitor (AI) in preserving the fertility of obese women with grade 1 endometrial cancer (EC). Methods This study recruited obese EC patients who wished to preserve their fertility. The treatment regimen consisted of intramuscular GnRH agonist 3.75 mg every 4 weeks and oral AI 2.5 mg daily. The maintenance regimen was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…After a median follow-up of four years, no recurrence was observed. The pregnancy rate was 50% and the life birth rate was 75% [ 74 ]. Tock et al, retrospectively, analyzed 18 women younger than 41 years with grade 1 EC (39%) or AEH (50%), who received endometrial resection and, subsequently, a GnRH agonist for three months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After a median follow-up of four years, no recurrence was observed. The pregnancy rate was 50% and the life birth rate was 75% [ 74 ]. Tock et al, retrospectively, analyzed 18 women younger than 41 years with grade 1 EC (39%) or AEH (50%), who received endometrial resection and, subsequently, a GnRH agonist for three months.…”
Section: Resultsmentioning
confidence: 99%
“…Estrogen withdrawal by the GnRH-agonist induced reversible medical castration, which has been used in combination with systemic or local progestogen application as a fertility sparing treatment for AEH and early EC [ 69 , 70 , 71 , 72 , 73 , 76 ]. Alternatively, GnRH agonists were combined with aromatase inhibitors for more intensive suppression of estrogens [ 73 , 74 , 76 ] or given alone after complete endometrial resection [ 75 ]. In these small series, complete response rates of about 70% (54–100%) were observed for early EC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obese patients are hyperestrogenic and suppressing the production of endogenous estrogen may be an effective alternative. A recent pilot study of a GnRH agonist combined with an aromatase inhibitor in fertility-sparing treatment of 6 obese women with grade 1 EC reported a complete response in all women at 3–6 months, and a pregnancy and live birth rate of 50% and 75% respectively [ 72 ]. A prospective observation study of LNG-IUD for 1 year plus a GnRH analogue for 6 months in patients aged <40 years with stage 1A EC showed results comparable to studies using MPA and MA, with a complete remission rate of 57% and a recurrence rate of 25% [ 73 ].…”
Section: Fertility-sparing Managementmentioning
confidence: 99%
“…A gonadotropin-releasing hormone (GnRH) agonist combined with another agent also can be used. Several studies have reported the successful treatment of EC with a GnRH agonist along with an aromatase inhibitor or LNG-IUS [ 16 , 41 , 42 ]. Additionally, others have reported positive outcomes of treatment incorporating photodynamic therapy [ 13 ] and of hysteroscopic resection of the lesion combined with progestin [ 43 ] or a GnRH agonist [ 44 ].…”
Section: Treatment Efficacy and Primary Modalitymentioning
confidence: 99%